Astragaloside IV: a potential nemesis for gastric cancer - Hu, Chao; Li, Qiong; Gong, Song-Nan; Zou, Xiao-Jie; Xu, Jia-Yue; Ying, Hai-Feng; Zheng, Lan (Frontiers in Pharmacology, 2025)
Gastric cancer (GC), a life-threatening malignancy with profound global health impacts, remains a cardinal focus of biomedical research. Recently, astragaloside IV (AS-IV), a bioactive triterpenoid saponin derived from Astragalus mongholicus Bunge, has garnered substantial attention for its multifaceted anticancer properties in preclinical investigations. This review systematically synthesizes current evidence on the molecular mechanisms underlying AS-IV’s inhibitory effects against GC, encompassing programmed cell death pathways (apoptosis, autophagy, pyroptosis, ferroptosis), tumor angiogenesis, tumor microenvironment modulation, Helicobacter pylori and inflammatory signaling networks. Many studies demonstrate that AS-IV can inhibit the development of GC through multi-target and multi-pathway mechanisms, making it a well-deserved nemesis of GC. Notably, although AS-IV has emerged as a potential candidate for GC therapy, it suffers from problems such as single research model, unclear toxic and side effects, and poor bioavailability. These seriously hinder the efficiency of AS-IV in the treatment of GC. In the future, we can design and implement a series of in vivo and in vitro experiments to further explore and clarify the mechanism of action of AS-IV in the treatment of GC. It is encouraged to carry out a number of high-quality clinical controlled studies to further prove the effectiveness and safety of AS-IV. In addition, we can also use emerging technologies (such as nanotechnology) to improve the bioavailability of AS-IV, bringing more hope to GC patients.